APPLICATION OF DIGITAL TELECOMMUNICATION ENVIRONMENT TO SOLVE LEGAL ISSUES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
At the given stage of development of mankind, the algorithm for acquisition and termination of the constitutional-legal status of an individual in different countries of the world is in a stage of active development in the digital telecommunications environment. This is facilitated by the relatively rapid changes that regularly occur in the internal legislation of different countries, the differences between them, and sometimes the contradictions in the regulatory acts in different countries. In some cases, this leads to the fact that at a certain point the algorithm for acquisition and termination of the constitutional-legal status of an individual in the digital telecommunications environment is already beginning to acquire the quality of stability, but new changes in the legislation again encourage us to start bringing different legal norms into line with each other, which is a complex process. Therefore, the guarantor of the balance of stability in the field of establishing the algorithm for acquiring and terminating the constitutional-legal status of an individual in the digital telecommunications environment may be precisely the idea of ​​the authors of modern legislative initiatives about when it is most reasonable to stop the constant changes in numerous legislative acts so that their end user can still apply them in practice. Otherwise, the domestic legislative system may irretrievably lose authority among the vast majority of citizens of the respective country, and the number of appeals to domestic and foreign courts to resolve numerous controversial issues will constantly increase more and more. As a result, the level of legal nihilism, which the relevant state bodies are rightly trying to fight at the moment, will also increase much faster than such problems will be solved. Moreover, the number of illegal actions will also increase not only in the virtual environment, but also in real life, as the rule for algorithmizing the actions performed by citizens of the respective country will come into force, both in the virtual environment and simultaneously in real space, which is a very complex process.